Preserving the Miami Marine Stadium (1962-64): tropical Brutalism, society of leisure, and ethnic identity - Lejeune, Jean-François (10º Seminário Docomomo Brasil, Curitiba, 2013, 2013)
Beginning in the 1930s in Southern Europe and spreading later in Latin America, a series of sport facilities were built in which the plastic and structural qualities of poured-in-place concrete were exploited to great visual and functional effect by architects like Pier Luigi Nervi, Eduardo Torroja, or Carlos Raúl Villanueva. All these buildings were part of a heroic period in the development of a Latin/Mediterranean approach and understanding of concrete, which contrasted with the rationalist canons of the International Style. Pier Luigi Nervi’s affirmation that every concrete structure constitutes “an organism within which all internal constraints are propagated and transmitted from a nervure to another” is not without paralleling the overall structure of the human body. Many of the structures mentioned above were indeed characterized by poured-in-place concrete and long-span cantilevered roofs whose expression of internal forces cannot be dissociated from the athlete’s muscles in tension. Less well known than its counterparts in Central and Latin America, and unique in the United States and in the world for its direct relation to a water stadium, the Miami Marine Stadium is a cast-in-place-concrete open building with a complex, multipart, paraboloid roof; it is 326-ft long and 108-foot with most of the widthcantilevered over the stands and the water stadium. The grandstand was designed by Hilario Candela—a Cuban architect who worked with Max Borges in Havana and SACMAG International in Puerto Rico and arrived in Miami in 1960 to join the historic firm of Pancoast, Ferendino, Grafton, Skeels and Burnham. After thirty years of continuous use for sport and entertainment events, the building was closed in 1992 following a biased engineering report. The grandstand was threatened by demolition for fifteen years until a public campaign for its preservation and reuse was launched in 2007-8 by the Friends of the Marine Stadium and DoCOMOMO-US/FL. Registered in September 2009 on the World Fund Watch List, the Grandstand has now been granted historic preservation status by the City of Miami but the integrity of its adjoining landscape remains under threat. Hilario Candela’s Marine Stadium epitomized further promises of a modern tropical urbanism and architecture that, using local techniques, materials, landscape and vastness of space, extolled Miami’s regional culture, climate and natural environment. The stadium was the opening act for an intense period of creativity for the firm and for Candela as a lead designer, a period that culminated with the South Dade campus of the Dade Junior College from 1964 to 1967. Illustrated with original photographs and drawings, the proposed paper will analyze the building and its structural system; outline the research process leading to its designation, and the challenges posed by the necessary changes of use of the structure;analyze the role played by the concept of “ethnic identity” and its convergence with landscape and architecture preservation interests for the preservation of one of the rarest expression of genuine Cuban/Latin American architectonic modernist influences within the postwar architecture of Miami.
Keywords: Concrete Construction; Miami; Ethnic Identity